2014
DOI: 10.1128/jcm.01996-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bruker Biotyper and Vitek MS Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry Systems for Identification of Mycobacteria Using Simplified Protein Extraction Protocols

Abstract: Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has recently been described as a fast and inexpensive method for the identification of mycobacteria. Although mycobacteria require extraction prior to MALDI-TOF MS analysis, previously published protocols have been relatively complex, involving significant hands-on time and materials not often found in the clinical laboratory. In this study, we tested two simplified protein extraction protocols developed at the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
124
2
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 35 publications
(55 reference statements)
4
124
2
4
Order By: Relevance
“…One microliter of the final supernatant was spotted in duplicate onto a 96-well polished stainless steel target plate and overlaid with 1 l of a saturated solution of ␣-cyano-4-hydroxycinnamic acid in 50% acetonitrile and 2.5% trifluoroacetic acid (both from Bruker Daltonics, Billerica, MA). Spectra were acquired in a linear positive-ion mode at a laser frequency of 60 Hz across a mass/charge (m/z) ratio of 2,000 to 20,000 with a MicroFlex LT mass spectrometer (Bruker Daltonics) as described previously (19). For each spectrum, 240 laser shots in 40-shot steps from different areas of the sample spot were accumulated and analyzed (automatic mode, default settings).…”
Section: Methodsmentioning
confidence: 99%
“…One microliter of the final supernatant was spotted in duplicate onto a 96-well polished stainless steel target plate and overlaid with 1 l of a saturated solution of ␣-cyano-4-hydroxycinnamic acid in 50% acetonitrile and 2.5% trifluoroacetic acid (both from Bruker Daltonics, Billerica, MA). Spectra were acquired in a linear positive-ion mode at a laser frequency of 60 Hz across a mass/charge (m/z) ratio of 2,000 to 20,000 with a MicroFlex LT mass spectrometer (Bruker Daltonics) as described previously (19). For each spectrum, 240 laser shots in 40-shot steps from different areas of the sample spot were accumulated and analyzed (automatic mode, default settings).…”
Section: Methodsmentioning
confidence: 99%
“…(8)(9)(10)(11). However, unlike most bacteria, which can be directly spotted onto a MALDI-TOF target plate, mycobacteria require inactivation and extraction steps prior to analysis, both for biosafety and for access to proteins in the cells.…”
mentioning
confidence: 99%
“…Furthermore, the effect of microorganism inactivation by heat has been evaluated, and it has been shown that the quality of the spectrum decreases with increasing temperature [24]. It was also recently reported that the conditions of microorganism cultivation also influence the spectrum [25] [26]. However, in another study, the effect of culture age, chilling or freezing the lysates and freeze-thaw cycles did not have any impact on spectrum quality [27].…”
Section: Introductionmentioning
confidence: 95%